O papel da biblioteca pública na efetivação dos direitos culturais: o caso da Biblioteca Pública Benedito Leite em São Luís - MA - SILVA, Aloma Samira da Cunha Martins (2018)
Discusses the role of Public Library Benedito Leite on execution of cultural rights. Therefore, the study begins with a focus on culture and cultural rights, its trajectory and conceptual basis. It identifies cultural rights in the 1988 Constitution and emphasizes cultural rights as fundamental rights. It follows conceptualizing public libraries, reporting the historical and functional text. Public libraries are seen as institutions that disseminate cultural goods. Finally, we try to identify Benedito Leite Library as a reference for the preservation and diffusion of cultural assets of the Maranhão literary culture. It was taken as methodological course, as to the nature of its objectives, the research of the descriptive type. Data collection was done through documentary research and, in relation to data analysis, the content analysis procedure was used. It is concluded that cultural rights are typified in the Brazilian legal system, enshrined in the 1988 Federal Constitution, in international treaties and can be identified as fundamental rights. It was identified that the Benedito Leite Public Library has worked with the work of the copyright office, so that the legal deposit is actually made, preserving the cultural memory. In terms of cultural offer, in terms of access, enjoyment and cultural diffusion, it has been found that it constantly works to provide the local community with accessibility, those with disabilities, and the improvement of their practices.It was highlighted the role that the Benedito Leite Public Library has in the Maranhão scenario as a diffuser of cultural rights, and in the effectiveness of these rights that are fundamental importance to reach a society increasingly aware of their rights and duties.